SCHOOL FAILURES - Henryk, NOGA (Trends in education, 2013)
School failures are connected with the discrepancies between the school teaching and educational requirements and students results and conduct. In the study different divisions of school failures were shown and various reasons for such failures, stemming both from inside and outside school, were presented. It was pointed that any success or failure at school is closely connected with a student's emotional development.
Keywords: school failures; didactics; education